Extravascular coagulation regulates haemostasis independently of activated platelet surfaces in an in vivo mouse model - Asuka Sakata; Kohei Tatsumi; Naoki Matsumoto; Nigel Mackman; Suguru Harada; Ryohei Kawasaki; Yukiko Okuyama-Nishida; Tetsuhiro Soeda; Keiji Nogami; Midori Shima (Communications Biology)
Abstract While the conventional understanding of haemostatic plug formation is that coagulation proceeds efficiently on the surface of activated platelets at the vascular injury site to form a robust haemostatic plug, this understanding does not explain the clinical reality that platelet dysfunction results in a mild bleeding phenotype, whereas coagulation disorders exhibit severe bleeding phenotypes, particularly in deep tissues. Here, we introduce an in vivo imaging method to observe internal bleeding and subsequent haemostatic plug formation in mice and report that haemostatic plug formation after internal bleeding, coagulation occurs primarily outside the blood vessel rather than on platelets. Experiments in mice with impaired platelet surface coagulation, depleted platelets, haemophilia A or reduced tissue factor expression suggest that this extravascular coagulation triggers and regulates haemostatic plug formation. Our discovery of the important role of extravascular coagulation in haemostasis may contribute to refining the treatment of haemostatic abnormalities and advancing antithrombotic therapy.